miR-199b-5p inhibits triple negative breast cancer cell proliferation, migration and invasion by targeting DDR1 - Wu, Anhao (Oncol Lett, 2018)
Triple negative breast cancer (TNBC) has received increasing attention from oncologists worldwide due to its poor prognosis and paucity of targeted therapies. MicroRNAs (miRs) are a group of small non-coding RNAs that are responsible for the post-transcriptional regulation of various target genes. The present study demonstrated that the expression of miR-199b-5p in breast cancer tissue was significantly reduced compared with that in normal breast tissues by reverse transcription-quantitative polymerase chain reaction. In addition, western blot analysis and luciferase reporter assays revealed that miR-199b-5p in TNBC cells inhibited discoidin domain receptor tyrosine kinase 1 expression by directly targeting its 3′-untranslated region. Furthermore, miR-199b-5p markedly suppressed the proliferation and invasion of TNBC cells, as demonstrated by using wound-healing, migration, invasion and proliferation assays. Collectively, these results indicate that miR-199b-5p may be a novel alternative therapeutic target for TNBC.